Keterkaitan Halal Knowledge, Halal Awareness, Halal Traceability dan Halal Purchase Intention pada Konsumen Tenun di Sumbar - Putri, Dina Agustin; Lita, Ratni Prima; Suziana, Suziana; Meuthia, Meuthia; Rahmi, Devi Yulia; Triani, Laura Amelia (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2024)
The study aims to analyze the influence of halal knowledge, halal awareness, and halal purchase intention, as well as halal traceability as moderating variables. This quantitative research used 150 respondents as samples selected purposively, namely weaving consumers in West Sumatra who understand information about halal weaving. Data was collected using a Google Form questionnaire using a 5-point Likert scale, and analyzed using SEM-PLS. The findings obtained are that halal knowledge has a significant positive effect on halal awareness; halal awareness has a significant positive effect on both halal traceability and halal purchase intention; and, halal traceability has a significant positive effect on halal purchase intention. Finally, halal traceability has been proven to fail to moderate the influence of halal awareness on halal purchase intention.